Treatment patterns and outcomes in older patients with advanced malignant pleural mesothelioma: Analyses of Surveillance, Epidemiology, and End Results‐Medicare data. Issue 9 (26th October 2021) - Danese, Mark D.; Daumont, Melinda; Nwokeji, Esmond; Gleeson, Michelle; Penrod, John R.; Lubeck, Deborah
Abstract: Background: Malignant mesothelioma is a rare neoplasm associated with asbestos exposure. Characterizing treatment patterns and outcomes of older patients with advanced malignant pleural mesothelioma (MPM) is important to understand the unmet needs of this population. Aim: To evaluate the demographic and clinical characteristics, treatment patterns, and outcomes among older patients diagnosed with advanced MPM in the United States between 2007 and 2013. Methods: This was a retrospective cohort study using Surveillance, Epidemiology, and End Results (SEER) data linked with Medicare claims. We included patients who were age 66 or older at the time of their primary MPM diagnosis between 2007 and 2013 and followed them through 2014. Treated patients who received first‐line chemotherapy with pemetrexed and platinum within 90 days of diagnosis, second‐line, or third‐line therapy were identified for evaluation of outcomes. Results: There were 666 older patients with advanced MPM, of whom 82% were male, 87% White, 78% stage IV, and 70% had no mobility limitation indicators at diagnosis. There were 262 patients who received first‐line chemotherapy for advanced MPM, most of whom (80%; n = 209) received pemetrexed‐platinum. Of these 209 patients, 41% ( n = 86) initiated second‐line therapy, and 26% ( n = 22) initiated third‐line therapy. Median overall survival for the cohort of 209 patients was 7.2 months. Patients with epithelioid histology had better median overall survival (12.2 months) compared with other histologies (4.4–5.6 months). Within 90 days of diagnosis of advanced MPM, 78% of patients were hospitalized, 52% visited an emergency department, and 21% had hospice care. The 2‐year cost of care was over 100 000 for all patients with advanced MPM treated with first‐line pemetrexed‐platinum. Conclusions: Although first‐line systemic anticancer treatment was generally consistent with guidelines (e.g., pemetrexed‐platinum), poor patient outcomes highlight the need for effective treatment options for older patients with advanced MPM.